The HSV-1 ICP4 Transcriptional Auto-Repression Circuit Functions as a Transcriptional “Accelerator” Circuit - Chaturvedi, Sonali; Engel, Ruth; Weinberger, Leor (Frontiers in Cellular and Infection Microbiology, 2020)
Herpes simplex virus-1 (HSV-1) is a significant human pathogen. Upon infection, HSV-1 expresses its immediate early (IE) genes, and the IE transcription factor ICP4 (infectious cell protein-4) plays a pivotal role in initiating the downstream gene-expression cascade. Using live-cell time-lapse fluorescence microscopy, we quantitatively monitored the expression of ICP4 in individual cells after infection. We find that extrinsic stimuli can accelerate ICP4 kinetics without increasing ICP4 protein levels. The accelerated ICP4 kinetics—despite unchanged steady-state ICP4 protein level—correlate with increased HSV-1 replicative fitness. Hence, the kinetics of ICP4 functionally mirror the kinetics of the human herpesvirus cytomegalovirus IE2 ‘accelerator’ circuit, indicating that IE accelerator circuitry is shared among the alpha and beta herpesviruses. We speculate that this circuit motif is a common evolutionary countermeasure to throttle IE expression and thereby minimize the inherent cytotoxicity of these obligate viral transactivators.